2014
DOI: 10.1248/cpb.c14-00320
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoids and Lignans from the Roots of <i>Syringa pinnatifolia</i>

Abstract: Two new sesquiterpenoids, pinnatifone A (1) and pinnatifone B (2), and two new lignans, pinnatifolin (3) and isopinnatifolin (4), along with six known lignans (5-10), were isolated from the roots of Syringa pinnatifolia. The structures of the new compounds were elucidated by extensive spectroscopic methods, including NMR, MS, UV, and IR spectra. The lignans were screened for their anti-oxidant activity (2,2-diphenyl-1-picrylhydrazyl (DPPH) assay). Most of them showed potent anti-oxidant activity, especially co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…6A–C). Previous studies found terpenes to be the major pharmacologically active substances in shanchenxiang [7,8,16], and our study found that the key enzyme of terpene biosynthesis was significantly upregulated in wild woody stems compared with cultivated woody stems; these results agree with the observation that the best shanchenxiang for medicinal use is collected from mature wild S. pinnatifolia plants, while the cultivated plants are less medicinally useful. Furthermore, HMGR was highly expressed in fibrous root tissue, which might be related to the environment in which such tissue develops; the fibrous roots are buried in soil, exposing them to a greater range of microorganisms and external stresses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…6A–C). Previous studies found terpenes to be the major pharmacologically active substances in shanchenxiang [7,8,16], and our study found that the key enzyme of terpene biosynthesis was significantly upregulated in wild woody stems compared with cultivated woody stems; these results agree with the observation that the best shanchenxiang for medicinal use is collected from mature wild S. pinnatifolia plants, while the cultivated plants are less medicinally useful. Furthermore, HMGR was highly expressed in fibrous root tissue, which might be related to the environment in which such tissue develops; the fibrous roots are buried in soil, exposing them to a greater range of microorganisms and external stresses.…”
Section: Discussionsupporting
confidence: 92%
“…Its peeled stems, roots, and twigs, called shanchenxiang in Chinese, are important in traditional Mongolian medicine [2], where they are used to treat palpitations, angina pectoris, myocardial ischemia, and other cardiovascular diseases [3].Researchers exploring the pharmacological properties of S. pinnatifolia have isolated and identified a variety of chemical compounds, including new lignans [4,5] and sesquiterpenes [6][7][8][9], as well as compounds known from other plants [10,11]. A number of these compounds, acquired from different tissues, exhibit pharmacological effects, including antibacterial [6,10], anti-inflammatory [10,12], antioxidant [4,8], antitumor [13], and cardioprotective [10] effects. The main compounds responsible for the pharmacological properties of S. pinnatifolia are the lignans and terpenes, with the sesquiterpenes showing the strongest effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previously described chemical characteristics, [12] components of ESO are mainly sesquiterpenoids, lignans, and essential oils, of which lignans have an overwhelming high content. On the basis of comparison with isolated compounds [24–31] and LC/MS data analysis shown in Figure 5, nine major constituents, in particular peaks 4, 7, and 8 were identified as syringin ( 1 ), isolariciresinol ( 2 ), cycloolivil ( 3 ), pinnatifolin A ( 4 ), alashinol G ( 5 ), alashinol F ( 6 ), secoisolariciresinol ( 7 ), lariciresinol ( 8 ), Z ‐pinnatifolin A ( 9 ), respectively. Their structures were shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%